2023
DOI: 10.1186/s12885-023-10806-5
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal chemotherapy combined with systemic therapy in patients with refractory leptomeningeal metastasis of non-small cell lung cancer: a retrospective study

Abstract: Background Leptomeningeal metastasis (LM) is the most devastating complication of non-small cell lung cancer (NSCLC), and its incidence is increasing. There is currently no standard treatment for LM, and the efficacy of traditional intravenous drug treatment is low, making refractory LM a difficult problem. In this study, we evaluated the efficacy and safety of intrathecal chemotherapy (IC)-based regimens in patients with refractory LM. Methods We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The drug is directly delivered to the subarachnoid space through lumbar puncture, which can make the drug evenly distributed along the subarachnoid space, directly act on the arachnoid and increase the drug concentration. Recently, more and more studies have shown that intrathecal injection has a good effect on tumor leptomeningeal metastasis, such as solid tumors such as breast cancer and lung cancer [11,15,[17][18][19]. All patients in this study were accompanied by obvious neurological symptoms, which seriously affected the quality of life of the patients.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The drug is directly delivered to the subarachnoid space through lumbar puncture, which can make the drug evenly distributed along the subarachnoid space, directly act on the arachnoid and increase the drug concentration. Recently, more and more studies have shown that intrathecal injection has a good effect on tumor leptomeningeal metastasis, such as solid tumors such as breast cancer and lung cancer [11,15,[17][18][19]. All patients in this study were accompanied by obvious neurological symptoms, which seriously affected the quality of life of the patients.…”
Section: Discussionmentioning
confidence: 93%
“…The main relevant factors reported were KPS score (median OS 12 months vs 6months), and high ECOG score was an important predictor of poor survival prognosis. Univariate analysis suggested that previous history of whole brain radiotherapy was associated with better prognosis, and multivariate analysis suggested that the combination of bevacizumab was an independent prognostic factor for intrathecal injection therapy [11,15,20,26]. The LM OS of ID2 combined with whole brain radiotherapy was signi cantly better than the median LM OS, suggesting that whole brain radiotherapy may be a prognostic factor affecting leptomeningeal metastasis of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation